Dystopia, Capitalism and Posthumanism in Tóquio(2021) by Daniel Galera - Leonardo-Loayza, Richard (2022)
The article proposes a reading of the novel Tóquio by Daniel Galera, which narrates, in a post-apocalyptic context, the story of a man who has received his mother's mind in a digital storage device; the dilemma of said man is to elucidate if what is stored there is really his mother or just a simulation. On this basis, it seeks to develop two objectives: the first, to analyze the peculiarities of this dystopia and its relationship with capitalism; the second, to establish the nature of the relationships that humans and posthumans (in this case, cybernetic entities) develop in this context of crisis.